Gaya Metaforis dalam Lirik Lagu di Album the Second Step: Chapter Two oleh Treasure - Dewi Ayu Lestari; Putu Dewi Merlyna Yuda Pramesti; Ni Nengah Suartini (Civiliza Publishing, Indonesia., 2026)
Song lyrics as a form of art not only function as a medium of entertainment, but also as a means of emotional expression and effective cultural representation. This study aimed to identify the forms and analyze the meanings of metaphorical figurative language in the song lyrics of the album The Second Step: Chapter Two by TREASURE. A qualitative descriptive approach in linguistics was applied in this research. Data were collected using observing, recording, and note-taking techniques. For the analysis of metaphor types and meanings, Knowles and Moon's (2006) theoretical framework was utilized, in which three main components (vehicle, topic, and ground) were focused upon. Based on the results, 15 metaphorical data from the seven analyzed songs were found, which were classified into metonymy (5 data), personification (4 data), simile (3 data), and synesthesia (3 data). Metonymy was shown to be the most dominantly used metaphor, indicating that conceptual contiguity associations were utilized to convey implicit messages. Furthermore, code-mixing elements were also found within the metaphor constructions, which were used to serve crucial semantic functions for emphasis and semantic precision due to the lack of lexical equivalents.